The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/ma13102222
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the Rotary Instrument XP-Endo Finisher in the Removal of Calcium Hydroxide Intracanal Medicament in Combination with Different Irrigation Techniques: A Microtomographic Study

Abstract: Objectives: This study aims to evaluate the efficacy of the rotary instrument XP-endo Finisher for the removal of Ca(OH)2 aided by different irrigation regimens. Methods: Sixteen double-rooted upper premolar human teeth were selected for the study. Thirty-two canals were prepared using a ProTaper Next rotary system up to X3. Then, the canals were filled with Ca(OH)2. The volume of Ca(OH)2 inside the canals was measured by microcomputed tomography (micro-CT). After that, the teeth were randomly allocated into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 35 publications
3
26
1
2
Order By: Relevance
“…Then, a total of 18 articles underwent a full-text screening. In this phase, nine [ 14 , 20 , 65 71 ] studies were excluded for the following reasons: five [ 14 , 65 , 68 , 70 , 71 ] lacked a comparison of medicament removal efficacy between the PUI group and XPF group, and four [ 20 , 66 , 67 , 69 ] did not evaluate outcomes according to the scoring system described by Lee et al or van der Sluis et al Finally, nine articles were included in the present systematic review and processed to data extraction [ 26 , 29 33 , 72 74 ]. Among the nine studies included for qualitative synthesis, one was not appropriate for the quantitative synthesis, because it just presented the minimum and maximum of the scoring results in the PUI and XPF group [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, a total of 18 articles underwent a full-text screening. In this phase, nine [ 14 , 20 , 65 71 ] studies were excluded for the following reasons: five [ 14 , 65 , 68 , 70 , 71 ] lacked a comparison of medicament removal efficacy between the PUI group and XPF group, and four [ 20 , 66 , 67 , 69 ] did not evaluate outcomes according to the scoring system described by Lee et al or van der Sluis et al Finally, nine articles were included in the present systematic review and processed to data extraction [ 26 , 29 33 , 72 74 ]. Among the nine studies included for qualitative synthesis, one was not appropriate for the quantitative synthesis, because it just presented the minimum and maximum of the scoring results in the PUI and XPF group [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…In simulated internal resorption cavities, XPF was superior to SNI, CB, and EA on the medicament removal [ 32 ]. XPF was more effective for removing calcium hydroxide residues than the XP-endo Shaper in extracted maxillary central incisors [ 14 ]. Moreover, in simulated immature root canals, the cleaning efficacy of XPF on medicaments removal was also better than SNI and EA [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…In simulated internal resorption cavities, XPF was superior to SNI, CB, and EA on the medicament removal [33]. XPF was more effective for removing calcium hydroxide residues than the XP-endo Shaper in extracted maxillary central incisors [15]. Moreover, in simulated immature root canals, the cleaning e cacy of XPF on medicaments removal was also better than SNI and EA [34].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have so far concluded that none of the applicable techniques was able to completely remove medicament substances from root canal regions [13][14][15]. It is urgent to compare the e cacy of various techniques in the removal of a root canal dressing, with the purpose of seeking the most effective irrigation method for clinical applications.…”
Section: Introductionmentioning
confidence: 99%
“…When the instrument is introduced into a canal, its shape memory and austenite phase conversion increase its effectiveness in touching and displacing root-filling materials. [ 9 10 11 12 13 14 15 16 ]…”
Section: Introductionmentioning
confidence: 99%